1993
DOI: 10.1021/jo00076a054
|View full text |Cite
|
Sign up to set email alerts
|

The invention of radical reactions. Part 32. Radical deoxygenations, dehalogenations, and deaminations with dialkyl phosphites and hypophosphorous acid as hydrogen sources

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(72 citation statements)
references
References 0 publications
2
68
0
2
Order By: Relevance
“…Fosfitos de alquila foram usados com sucesso 114 como redutores em reações de desoxigenação de tionocarbonatos e de xantatos de álco-ois primários e secundários. Peróxido de benzoíla foi utilizado como iniciador, o que não é problema em pequena escala mas dificulta o trabalho no caso do uso de quantidades maiores de reagentes 114,115 . Outros compostos de fósforo (III) empregados foram: ácido fosforoso, H 3 PO 2 , e seus sais.…”
Section: Desoxigenações Radicalares: O Método De Barton-mccombieunclassified
See 1 more Smart Citation
“…Fosfitos de alquila foram usados com sucesso 114 como redutores em reações de desoxigenação de tionocarbonatos e de xantatos de álco-ois primários e secundários. Peróxido de benzoíla foi utilizado como iniciador, o que não é problema em pequena escala mas dificulta o trabalho no caso do uso de quantidades maiores de reagentes 114,115 . Outros compostos de fósforo (III) empregados foram: ácido fosforoso, H 3 PO 2 , e seus sais.…”
Section: Desoxigenações Radicalares: O Método De Barton-mccombieunclassified
“…Normalmente, as reações são feitas em presença de uma amina terciária, para proteger grupos sensíveis a ácidos que estejam presentes na molécula. Ácido hipofosforoso não é aplicável a substratos sensíveis à umidade devido às dificuldades de completa remoção da água presente no reagente 115,116 . Um diol vicinal, 1,2;5,6-di-O-isopropilidenomanitol, foi desoxigenado à olefina correspondente em 78% de rendimento através do seu respectivo bisxantato, pelo uso de ácido fosforoso/trietilamina.…”
Section: Desoxigenações Radicalares: O Método De Barton-mccombieunclassified
“…On the other hand, compounds of the ϾP(O)H structure can act as proton [19,20] or hydrogen [21,22] sources, depending on the structure and reaction conditions. Recently, we have been able to demonstrate that the anions of the ϾP-O ‫מ‬ type undergo a reaction with ␣-bromocarboxylates as well as with phosphonates yielding debrominated products [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[1] In particular, the stability of P-centered radicals has facilitated the use of phosphorus hydrides as surrogates for tin hydrides. [2][3][4][5][6] Furthermore, the addition of phosphinyl, [7] phosphinoyl, [8][9][10][11][12] and phosphonyl [13,14] radicals, as well as their sulfur-containing counterparts, [15][16][17] to alkenes is a widely used method for the preparation of organophosphorus compounds and polymers.…”
mentioning
confidence: 99%
“…In 1988, Nugent and RajanBabu reported that [Cp 2 TiCl] was able to transfer one electron to oxiranes with formation of b-titanoxy radicals, which could be used further in syntheses. [27] This seminal work was made even more useful when Gansäuer et al rendered this reaction catalytic, [28] and soon thereafter asymmetric.…”
mentioning
confidence: 99%